THE ROLE OF SOCIAL SUPPORT AND EDUCATION LEVEL IN ADHERENCE TO ANTI-RETROVIRAL (ARV) DRUGS IN HIV/AIDS PATIENTS: NARATIVE REVIEW - Girsang, Jakasmir; Nababan, Tiarnida; Ikhtiari, Refi (Nurse and Holistic Care, 2025)
Background: Adherence to antiretroviral (ARV) therapy is essential for effective HIV/AIDS management. Social support and patients’ education levels have been shown to influence treatment adherence. Objective: To review the role of social support and education in adherence to ARV medication among people living with HIV/AIDS (PLWHA). Methods: This study is a narrative literature review. Articles were retrieved from Google Scholar using predefined inclusion and exclusion criteria. The quality of the selected studies was assessed using the JBI Critical Appraisal Checklist, and findings were synthesized thematically. Results: Ten articles met the inclusion criteria (n = 10). Most studies reported that family support and higher education levels were positively associated with better adherence to ARV therapy. Conclusion: Social support and education are key determinants of ARV adherence. Interventions that emphasize patient education and family involvement are recommended to improve treatment outcomes in PLWHA.